Urinary 8-oxodeoxyguanosine levels in children exposed to air pollutants - Svecova, Vlasta; Rossner, Pavel; Dostal, Miroslav; Topinka, Jan; Solansky, Ivo; Sram, Radim J (Mutation research, 2009)
Oxidative stress is believed to be one of the mechanisms of effects of air pollution to human health. We investigated levels of 8-oxodeoxyguanosine (8-oxodG), a marker of oxidative damage to DNA, in urine samples of 894 children from two districts in the Czech Republic: Teplice and Prachatice. We assessed the association between 8-oxodG levels and exposure to particulate matter of different size: <or=10 microm (PM10), <or=2.5 microm (PM2.5) and carcinogenic polycyclic aromatic hydrocarbons (c-PAHs); as well as between 8-oxodG levels and individual lifestyle, health and pregnancy outcomes. An ELISA technique was used for analysis of 8-oxodG levels. Median levels (range) of 8-oxodG in children from Teplice vs. Prachatice were as follows: 14.6 (3.1-326.5) nmol/mmol vs. 15.2 (3.0-180.8) nmol/mmol creatinine (p=0.34). Levels of 8-oxodG were elevated in children exposed to environmental tobacco smoke (ETS) (p<0.05) and among the Gypsy population (p<0.01). Levels of 8-oxodG decreased with the child's age (p<0.001) and increasing level of the mother's education (p<0.01). Multivariate statistical analyses confirmed the effect of the child's age and ETS exposure on 8-oxodG levels. The exposure to PM10 and PM2.5 measured by stationary monitors during a 7-day period before urine collection, as well as the exposure to c-PAHs measured during 3-day periods 1-3 and 7-9 days before urine collection were identified as factors affecting 8-oxodG levels in multivariate models. The obtained results indicate that 8-oxodG is a sensitive biomarker for measuring the exposure of children to air pollution.
Keywords: pevné částice; Humans; Deoxyguanosine; dítě; Child; vystavení vlivu životního prostředí; lidé; Air Pollutants; Regression Analysis; Particulate Matter; látky znečišťující vzduch; předškolní dítě; 8-Hydroxy-2'-Deoxyguanosine; deoxyguanosin; Czech Republic; Environmental Exposure; 8-hydroxy-2'-deoxyguanosin; Česká republika; Child, Preschool; regresní analýza